2010
DOI: 10.1002/qre.1165
|View full text |Cite
|
Sign up to set email alerts
|

Examining improved experimental designs for wind tunnel testing using Monte Carlo sampling methods

Abstract: Wind tunnels are used in the design and testing of a wide variety of systems and products. Wind tunnel test campaigns involve a large number of experimental data points, can take a long time to accomplish, and can consume tremendous resources. Design of Experiments is a systematic, statistically based approach to experimental design and analysis that has the potential to improve the efficiency and effectiveness of wind tunnel testing. In Defense Acquisition, wind tunnel testing of aircraft systems may require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Additional details on the phase I aspect of this study are found in Hill et al 12 and research awards, including the Outstanding…”
Section: Notementioning
confidence: 99%
“…Additional details on the phase I aspect of this study are found in Hill et al 12 and research awards, including the Outstanding…”
Section: Notementioning
confidence: 99%
“…The partitioning of the data into transonic and supersonic subspace design regions enabled the fitting of low-order polynomial models. As such, Hill et al 4 limited the models to full quadratic models and pure cubic terms.…”
Section: Case Studymentioning
confidence: 99%
“…Hill et al 4 proceeded to generate response surface models for both the transonic and supersonic design regions using approximately 900 experimental design points of two alternative designs (Nested Face-Centered Design (NFCD) and an I -optimal computer-generated design) by sampling from the “ground truth” model with an N ( 0 , 0 . 0125 ) error added. They then compared the corresponding surfaces using a Monte Carlo sampling methodology coupled with a statistical comparison to determine the functional equivalency of the surfaces.…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations